Criticise of Van Zuidam Classification: A Purpose of Landform Unit - T. Listyani R.A. Listyani (Retii, 2019)
The classification of landscapes has been put forward by many experts in geomorphology. One classification commonly used is the Van Zuidam classification. With various interpretations of the reader, the use of this classification is often debated. This paper wants to mediate the differences of opinion or diversity of interpretations by modifying the landscape classification of Van Zuidam (1983) and Van Zuidam - Cancelado (1979). Several constraints which constitute the shortcomings and advantages of classification were raised to clarify this critique process. The process of unifying the landscape is also expected to be more easily understood and adjust the standard Indonesian language rules. The procedure for determinating landscape units can be done with various parameters but it should be done with procedures that mainly consider the contour pattern and genetic similarity of the landscape. This paper proposes the existence of 17 sub-classes as details of 7 main morphometric classes made by Van Zuidam & van Zuidam-Cancelado (1979).